دراسة تألق البراسيوديميوم المشوب في مركبات الفلورايد المحرضة بالأشعة السينية (Latakia University Journal -Basic Sciences Series, 2018)
يعدّ هذا العمل استمراراً لدراسة أطياف تألق الإصدار التعاقبي لإيون البراسيوديميوم Pr3+ في قوالب متنوعة، فقد قمنا بدراسة هذه الأطياف لبلورة فلور الباريوم النقية والمشوبة بإيون البراسيودسميوم Pr3+ بالمقدارين 0.3% وَ 3%. أظهرت الدراسة القمم الطيفية المميزة 480nm, 392nm, 300nm والمقابلة لزمني تلاشٍ، الأول سريع 39ns والثاني بطيء 690ns، تم التركيز على مراكز التألق الممثلة بالانتقالين المشعين 1S0→1I0 كمرحلة أولى وَ 3P0→3Fj, 3Hj كمرحلة ثانية. وأخيراً تم استعراض الكمون المتوقع للمغنيزيوم ودراسته كمعوض شحنة للبراسيوديميوم في المركب SrAlF5.  تستخدم هذه البلورات في الأجهزة الليزرية وفي العددادات الوميضية. أجريت القياسات في جامعة بطرس بورغ التكنولوجية الحكومية- روسيا الاتحادية عام 2006. This work is a continuation of a study of the Pr3+ cascade emission in various matrices. The emission and excitation spectra of BaF2 doped with 0.3 and 3% Pr3+ were obtained. All spectra contain a broad band peaking at about 300nm, 392nm, 480nm. The fast one with a decay constant of 39 ns, and the slow one with a decay constant of 690 ns. The effect of the environment of the luminescence center, consists of two consecutive radiative transitions 1S0→1I0 (the first stage), and 3P0→3Fj, 3Hj (the second stage). The expecting potential of magnesium as a charge compensator for praseodymium in SrAlF5 is demonstrated. These crystals could be used in LASER equipments and in Luminescence Counters. The measurements were done in Tech-governmental University of Petersburg- Russia, in year 2006.